Desain Materi Ajar Berbasis Adobe Flash CS6 untuk Meningkatkan Minat Belajar Bahasa Arab Mahasiswa IAIN Ponorogo - Muhammad Nasrullah; Achmad Baihaqi (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
The teaching process is now more focused on interactive media-based learning technology such as CDs, laptops and the Internet, but nowadays many teachers still maintain and use media only based on textbooks, so learning Arabic tends to be boring and student interest is very low. GMI.B students are the average graduates from public schools (SMK and SMA). The purpose of this study was to increase student interest in learning Arabic by designing teaching materials based on Adobe Flash CS6. This study uses the type of research R&D (Research Development) with the ADDIE model, data is collected using observation, interviews, documentation, questionnaires and check lists techniques and then analyzed qualitatively and quantitatively descriptively with (T.test) test. t. Design of teaching materials for Arabic learning based on Adobe Flash CS6 for GMI.B students. The material expert validation stage and media expert validation both gave a score of "very good" and the product design of the textbook was declared "feasible" to be used as an Arabic language learning media application. The results of the pre-test test of interest in learning Arabic for GMI.B IAIN Ponorogo students before using the design of Arabic learning teaching materials based on Adobe Flash CS6 resulted in an average of 75.88. While the results of the post-test test of interest in learning Arabic for GMI.B IAIN Ponorogo students after using the design of Arabic learning teaching materials based on Adobe Flash CS6 resulted in an average of 87.88. Based on these results, it can be concluded that the use of Adobe Flash CS6-based Arabic learning teaching materials can effectively increase interest in learning Arabic for GMI.B IAIN Ponorogo students. Abstrak Proses pengajaran sekarang lebih menitik beratkan pada teknologi pembelajaran berbasis media interaktif seperti CD, laptop dan Internet, tetapi dewasa ini banyak juga pengajar yang masih mempertahankan dan menggunakan media hanya bersumber pada buku teks, sehingga pembelajaran bahasa Arab cenderung membosankan dan minat mahasiswapun sangat rendah. Mahasiswa GMI.B adalah rata-rata lulusan dari sekolah umum (SMK dan SMA). Tujuan penelitian ini adalah untuk meningkatkan minat mahasiswa dalam belajar bahasa Arab dengan desain materi ajar berbasis Adobe FlashCS6. Penelitian ini menggunakan jenis penelitian R&D (Research Development) dengan model ADDIE, data dikumpukan dengan tehnik observasi, wawancara, dokumentasi, angket dan check list kemudian dianalisis secara kualitatif dan kuantitatif-deskriptif dengan (T.test) Uji. t. Desain materi ajar pembelajaran bahasa Arab berbasis Adobe FlashCS6 bagi mahasiswa GMI.B. Tahap validasi ahli materi dan validasi ahli media keduanya memberikan skor “sangat baik” dan desain produk buku ajar dinyatakan “layak” untuk dipergunakan sebagai aplikasi media pembelajaran bahasa Arab. Hasil pengujian pre test minat belajar bahasa Arab mahasiswa GMI.B IAIN Ponorogo sebelum penggunaan desain materi ajar pembelajaran bahasa Arab berbasis Adobe FlashCS6 menghasilkan rata-rata sebesar 75,88. Sedangkan hasil pengujian post test minat belajar bahasa Arab mahasiswa GMI.B IAIN Ponorogo sesudah penggunaan desain materi ajar pembelajaran bahasa Arab berbasis Adobe FlashCS6 menghasilkan rata-rata sebesar 87,88. Berdasarkan hasil tersebut dapat disimpulkan bahwa penggunaan desain materi ajar pembelajaran bahasa Arab berbasis Adobe FlashCS6 efektif dapat meningkatkan minat belajar bahasa Arab mahasiswa GMI.B IAIN Ponorogo